2018
DOI: 10.1111/ppc.12301
|View full text |Cite
|
Sign up to set email alerts
|

The effect of motivational interviews on treatment adherence and insight levels of patients with schizophrenia: A randomized controlled study

Abstract: MI can be included during any of the patient visits to establish treatment collaboration with psychiatric patients at psychiatric facilities, outpatient clinics, and community mental health centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…Medical employees here, including doctors, nurses and other hospital staffs need to give psychoeducation to the patient for being aware of their illness and know their symptoms further. (24) Besides, the medical staffs are required to give a nice, improved and secured hospital environment especially during the pandemic so it expected to reduce the patient's fear to come to the hospital. (25) The Intervention of psychoeducation for patients with schizophrenia disorders shows some improvements outcome to the patient especially for very long-term inward patient.…”
Section: Discussionmentioning
confidence: 99%
“…Medical employees here, including doctors, nurses and other hospital staffs need to give psychoeducation to the patient for being aware of their illness and know their symptoms further. (24) Besides, the medical staffs are required to give a nice, improved and secured hospital environment especially during the pandemic so it expected to reduce the patient's fear to come to the hospital. (25) The Intervention of psychoeducation for patients with schizophrenia disorders shows some improvements outcome to the patient especially for very long-term inward patient.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that MI, another intervention branch integrated in this study, focuses rather on clinical recovery in schizophrenia. Even though it is not possible to talk about a common conclusion for all these studies (Chien et al, 2016;Chien et al, 2015;Ertem & Duman, 2019;Kreyenbuhl et al, 2016;Vanderwaal, 2015), some randomized controlled studies found that MI improved treatment compliance and reduced psychotic symptoms and hospitalizations in IDSs (Chien et al, 2015(Chien et al, , 2016Ertem & Duman, 2019). Given the fact that clinical recovery in IDSs is an important stage in functional recovery (Lahera et al, 2018), the significance of MI is certainly understood much better.…”
Section: Discussionmentioning
confidence: 99%
“…Although both therapies advocate different treatment philosophies and models, they actually achieved significant results in some areas that will constitute the content of functional recovery in IDSs. For example, MI contributes to functional recovery by providing treatment motivation and cognitive rehabilitation mostly in IDSs (Ertem & Duman, 2019; Fiszdon et al, 2016), while ACT seems to contribute to functional recovery by decreasing the rate of hallucination-related distress, anxiety, depression and hospitalization (Ridenour et al, 2019; Yıldız, 2020). For this reason, there may be psycho-social approaches that produce pragmatic results in supporting functional recovery by acting jointly with ACT and MI.…”
Section: Introductionmentioning
confidence: 99%
“…Significant intergroup differences were found in the T1 period (P = 0.045) based on the hypothesis that in the MI group wheel values are significantly higher than those in the TAU group. (Ertem & Duman, 2019).…”
Section: Change Wheel Scalementioning
confidence: 99%
“…In the validation of the terminology, MI followed the model of Miller & Röllnick (2015) and correlates with three NANDA-I diagnoses: & Sanz, 2015;Dobber et al, 2018;Ertem & Duman 2019;Xu et al, 2019).…”
Section: Ta B L E 1mentioning
confidence: 99%